Optimalisasi Pengelolaan dan Pemanfaatan Sampah Oleh Mahasiswa KKN Uniwara di Kelurahan Bugul Kidul - Aulia, Darojatul (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Waste management has become a crucial issue amidst the increasing population and modern consumption, which has led to a surge in the amount of waste, both organic and inorganic. Plastic waste, which takes a long time to decompose, is a significant environmental challenge. The Real Work Lecture (KKN) Program of Universitas PGRI Wiranegara in Bugul Kidul Village aims to increase public awareness of the importance of optimizing waste management and utilization, which in this case is carried out through socialization and recycling innovation. This activity involves socialization regarding the impact of waste and the introduction of recycled products from plastic waste, including the creation of works of art from waste, such as recycled dresses. The results of the activity showed high public enthusiasm, which is expected to contribute to increasing their participation in better waste management. With a creative approach to waste processing, the community is not only taught to recycle but is also encouraged to see waste as a potential resource that can produce useful products. This KKN activity has a positive impact in increasing environmental awareness and sustainability through more optimal waste management and utilization.